Hydroxamate production as a high affinity iron acquisition mechanism in Paracoccidioides Spp. - Bailão, Mirelle Garcia Silva (2014)
Iron is a micronutrient required by almost all living organisms, including fungi. Although this metal is abundant, its bioavailability is low either in aerobic environments or within mammalian hosts. As a consequence, pathogenic microorganisms evolved high affinity iron acquisition mechanisms which include the production and uptake of siderophores. Here we investigated the utilization of these molecules by species of the Paracoccidioides genus, the causative agents of a systemic mycosis. It was demonstrated that iron starvation induces the expression of Paracoccidioides ortholog genes for siderophore biosynthesis and transport. Reversed-phase HPLC analysis revealed that the fungus produces and secretes coprogen B, which generates dimerumic acid as a breakdown product. Ferricrocin and ferrichrome C were detected in Paracoccidioides as the intracellular produced siderophores. Moreover, the fungus is also able to grow in presence of siderophores as the only iron sources, demonstrating that beyond producing, Paracoccidioides is also able to utilize siderophores for growth, including the xenosiderophore ferrioxamine. Exposure to exogenous ferrioxamine and dimerumic acid increased fungus survival during co-cultivation with macrophages indicating that these molecules play a role during host-pathogen interaction. Furthermore, cross-feeding experiments revealed that Paracoccidioides siderophores promotes growth of Aspergillus nidulans strain unable to produce these iron chelators. Together, these data denote that synthesis and utilization of siderophores is a mechanism used by Paracoccidioides to surpass iron limitation. As iron paucity is found within the host, siderophore production may be related to fungus pathogenicity.